(untitled) (Journal of Forensic Medicine & Toxicology, 2020)
Assessing the height of an individual, from measurements of different parts, has always been of immense interest to forensic medicine experts. Aim of the present study was to estimate stature from clavicle length of both side and compare the correlation coefficient in both sexes. This study was carried out on 200 medico-legal autopsies which were brought to Forensic Medicine Department, M. P. Shah Govt. Medical College, Jamnagar during the period of January 2014 to December 2014. The mean stature of male was 1692.59±85.13 mm and in female was 1566.89±57.49 mm. Mean right clavicle length in male was 143.66±10.06 while in female was 130.89±9.28. Mean left clavicle length in male was 142.35±10.18 while in female was 129.50±9.64. Correlation co-efficient for both clavicle in males and females were > 0.5. Males were taller and have longer clavicle than females. There was large correlation between height and clavicle length in both males and females. Correlation co-efficient for male for right clavicle was higher than females so, stature prediction from right clavicle length was more accurate in males than females.